Sex discrimination in the public sector. A study of the law of employment / Sharina Saidon - Saidon, Sharina (Faculty of Law, 1983)
The object of this paper is :- To study whether discrimination based on sex exists in the area of employment in the Public Sector. This paper has been divided into three main chapters. In Chapter I, a definition of the term 'discrimination* is given. Legislation which guarantees equal rights of citizens in different countries is compared. A study as to whether sex discrimination is unconstitutional has also been carried out. •In Chapter II a discussion pertaining to employment in the Public Sector is carried out. Each aspect of employment - equal pay, promotions, working hours( privileges, loans and transfer — are studied and analysed in accordance with the statistics obtained from the various divisions of the Public Service Department. For each sub-topic, an examination and analysis of the contemporary position is made together with proposals for reform. Chapter III examines the economic and social implications of discrimination against women. In conclusion, the writer has also commented on the role of women in the development of the nation.